2020
DOI: 10.1111/jocs.14424
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic aortic arch injury after unsuccessful percutaneous tracheostomy

Abstract: Tracheostomy is a procedure that creates a direct opening to the airway through an incision in the anterior wall of the trachea. These days it is usually performed percutaneously as it is generally regarded as a safe procedure. We present the case of an unusual complication of aortic arch injury after percutaneous tracheostomy (PT) performed at an outside hospital. Major vascular injury was managed with sternotomy and direct aortic repair with a successful outcome. We believe PT should be performed under direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, aortic arch injury has been reported as an infrequent complication. [ 13 ] In this context, anticoagulation and continuation of heparinization are both debated in cardiac surgery patients, particularly in patients who require extracorporeal life support. Bektas et al[ 14 ] reported that PDT could be applied safely in patients with extracorporeal membrane oxygenation and/or left ventricular assist device, and no significant complications were encountered in the bedside PDT procedure in the patients with a mean INR value of 2 to 3.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aortic arch injury has been reported as an infrequent complication. [ 13 ] In this context, anticoagulation and continuation of heparinization are both debated in cardiac surgery patients, particularly in patients who require extracorporeal life support. Bektas et al[ 14 ] reported that PDT could be applied safely in patients with extracorporeal membrane oxygenation and/or left ventricular assist device, and no significant complications were encountered in the bedside PDT procedure in the patients with a mean INR value of 2 to 3.…”
Section: Discussionmentioning
confidence: 99%